Structural behavior and design criteria of extradosed bridges: general insight and state of the art - Benjumea, José; Maldonado, Esperanza (Revista Ingeniería de Construcción, 2010)
Over the past 10 years, Extradosed bridges have become an attractive structural type around the world, due to the good results obtained with the first bridges constructed in Japan. This new typology, generally recognized as an intermediate solution between cable stayed bridges and cantilever constructed prestressed box-girder bridges, because these take advantages of design and constructions methods of the other two typologies, has become an interesting option. Therefore, given the interest that exist about this type of bridge, in this paper the historical context that describes its origin, the influence of the principal structural elements and the design criteria proposed by researchers are presented. In this way it is expected to offer a general insight into the design conception and structural behavior of Extradosed Bridges, so that they may be considered as an alternative structure for bridges in the Americas.